Keratinocyte growth factor for the treatment of the acute respiratory distress syndrome (KARE): a randomised, double-blind, placebo-controlled phase 2 trial. Issue 6 (June 2017) - McAuley, Daniel F; Cross, LJ Mark; Hamid, Umar; Gardner, Evie; Elborn, J Stuart; Cullen, Kathy M; Dushianthan, Ahilanandan; Grocott, Michael PW; Matthay, Michael A; O'Kane, Cecilia M
Summary: Background: Data from in-vitro, animal, and human lung injury models suggest that keratinocyte growth factor (KGF) might be beneficial in acute respiratory distress syndrome (ARDS). The objective of this trial was to investigate the effect of KGF in patients with ARDS. Methods: We did a double-blind, allocation concealed, randomised, placebo-controlled phase 2 trial in two intensive care units in the UK, involving patients fulfilling the American-European Consensus Conference Definition of ARDS. Patients were randomly assigned (1:1) by computer-generated randomisation schedule with variable block size stratified by site and presence of severe sepsis requiring vasopressors to receive either recombinant human KGF (palifermin 60 μg/kg) or placebo (0·9% sodium chloride solution) daily for a maximum of 6 days. Both patients and investigators were masked to treatment. The primary endpoint was oxygenation index (OI) at day 7. Analyses were by intention to treat. The trial is registered with International Standard Randomised Controlled Trial Registry, number ISRCTN95690673. Findings: Between Feb 23, 2011, and Feb 26, 2014, 368 patients were assessed for eligibility for inclusion in the trial. Of the 60 patients recruited, 29 patients were randomly assigned to receive KGF and 31 to placebo; all were included in the analysis of the primary outcome. There was no significant difference between the two groups in OI at day 7 (mean 62·3 [SD 57·8] in the KGF group, 43·1 [33·5] in the placebo group; mean difference 19·2, 95% CI −5·6 to 44·0, p=0·13). Of interest, although not defined as outcome measures a priori, the KGF group, compared with placebo, had fewer median ventilator-free days (1 day [IQR 0 to 17] in the KGF group vs 20 days [13–22] in the placebo group; difference −8 days, 95% CI −17 to −2; p=0·0002), a longer median duration of ventilation in survivors to day 90 (16 days [IQR 13–30] in the KGF group vs 11 days [8–16] in the placebo group; difference 6 days, 95% CI 2 to 14; p=0·002), and a higher mortality at 28 days (nine [31%] vs three [10%] deaths; risk ratio 3·2, 95% CI 1·0 to 10·7, p=0·054). Adverse events were more frequent in the KGF group than the placebo group (14 vs 5 events; odds ratio 4·9, 95% CI 1·3 to 20·3, p=0·008). The two adverse events assessed as related to KGF were due to pyrexia. Interpretation: KGF did not improve physiological or clinical outcomes in ARDS and might be harmful to patient health. Funding: The Northern Ireland Public Health Agency Research and Development Division.